Lipopolysaccharide impairs insulin sensitivity via activation of phosphoinositide 3-kinase in adipocytes. (April 2014) - Wakayama, Sayori; Haque, Abedul; Koide, Naoki; Kato, Yoshiro; Odkhuu, Erdenezaya; Bilegtsaikhan, Tsolmongyn; Naiki, Yoshikazu; Komatsu, Takayuki; Yoshida, Tomoaki; Yokochi, Takashi
Abstract The effect of lipopolysaccharide (LPS) on insulin sensitivity in adipocytes were examined by using differentiated 3T3-L1 adipocytes. Insulin-mediated activation of insulin receptor substrate (IRS) 1/2 was inhibited in LPS-pretreated adipocytes and IRS1/2-mediated Akt activation was also attenuated in those cells. LPS inhibited activation of glycogen synthase kinase 3 as a negative regulator of glycogenesis and impaired the glycogen synthesis in response to insulin. LPS-induced activation of phosphoinositide 3-kinase (PI3K) in adipocytes. Involvement of suppressor of cytokine signaling 3 (SOCS3) in LPS-induced IRS1/2 inhibition was excluded. Considering that both insulin and LPS were able to activate the PI3K/Akt signaling pathway, LPS was suggested to impair insulin sensitivity of adipocytes through down-regulating insulin-mediated PI3K/Akt activation.